Pengembangan E-Modul Berbasis Forward and Backward Chaining dalam Peningkatan Kemandirian Belajar - Jonvi, Putra Novempra; Munir, Sirajul; David, David; BS, Iman Asroa (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This research is motivated by the lack of independence in student learning because the teaching materials used are less varied and insufficient in number for students. Besides that, there are also limitations of existing teaching materials in empowering students to learn. The research aims to develop e-modules based on Forward and Backward Chaining that are valid and practical to use. The research was carried out by developing E-modules which were then validated and practiced in learning. Research data was collected using validation sheets for expert assessment and student response questionnaires for module practicality assessment. The validation data obtained was processed using the Aiken's V formula and the practicality data was processed using the Degree of Achievement formula. The results of this study state that the developed E-module is very valid to use with a value of 0.91 and very practical to use in learning with a value of 87.8. Thus, this module can be used for PAI learning activities at the public junior high school level in Tanjung Baru District.